Konsekuensi Hukum Kekerasan dalam Rumah Tangga terhadap Tingkat Perceraian: Perspektif Hukum Islam dan Positif - Ubaidillah, Asep (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2023)
This research discusses "The Legal Consequences of Domestic Violence on Divorce Rates" by considering Islamic and positive legal perspectives in the Tangerang City Religious Courts. Qualitative research methods with a case study approach are used to understand the complex phenomenon of domestic violence and divorce in more depth and contextually. Data was collected through interviews with the parties involved, including divorce applicants, domestic violence victims, Religious Court judges, and lawyers. Data was also obtained from legal documents related to domestic violence and divorce cases. The research results reveal the main conclusions. First, factors causing domestic violence include weak mental quality, lack of religious values, low education, an unsupportive family environment, and lack of moral values. Second, the role of the family environment in shaping a person's behavior, especially children, is in the spotlight. An abusive and aggressive family environment can contribute to similar behavior in domestic relationships as an adult. This research provides a deeper understanding of the impact of domestic violence on divorce and illustrates the complexity of this issue in the context of Islamic and positive law.